2022
DOI: 10.1186/s13722-022-00333-2
|View full text |Cite
|
Sign up to set email alerts
|

Formal mindfulness practice predicts reductions in PTSD symptom severity following a mindfulness-based intervention for women with co-occurring PTSD and substance use disorder

Abstract: Background Women with co-occurring posttraumatic stress disorder (PTSD) and substance use disorder (SUD) experience systemic barriers that place them in danger of poorer treatment outcomes. Some mindfulness-based interventions (MBIs) have demonstrated efficacy in reducing PTSD and SUD symptoms. Mindfulness practice is a core component of MBIs, thought to elicit and maintain positive behavioral change; however, no research to our knowledge has assessed the role of mindfulness practice on sustained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Furthermore, systematic reviews on mindfulness-based interventions for PTSD showed medium to large effect size, but its effect on individuals with this comorbidity is unknown [23]. The studies that have looked at mindfulness interventions specific to concurrent PTSD-SUD showed potential benefits in terms of PTSD outcome but not substances' craving and some were small in size and for specific sub-population (i.e., women only) [24][25][26]. There is a crucial need for the advancement of treatments focused on the unique needs of this comorbid group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, systematic reviews on mindfulness-based interventions for PTSD showed medium to large effect size, but its effect on individuals with this comorbidity is unknown [23]. The studies that have looked at mindfulness interventions specific to concurrent PTSD-SUD showed potential benefits in terms of PTSD outcome but not substances' craving and some were small in size and for specific sub-population (i.e., women only) [24][25][26]. There is a crucial need for the advancement of treatments focused on the unique needs of this comorbid group.…”
Section: Discussionmentioning
confidence: 99%
“…Mind-body interventions are reported as effective for a vast range of clinical conditions [4][5][6][7][8][9][10] and are also successfully translating into technology-driven healthcare [11][12][13][14]. The properties/structure of mind-body medicine also imply that they are meaningfully compatible with augmented reality/AR as telehealth develops into the future.…”
Section: Extant Purview Of Mind-body Medicine and Clinical Outcomesmentioning
confidence: 99%